Putting it all together: Aggregating impacts of school-feeding programmes on education, health and nutrition: two proposed methodologies - Aulo Gelli; Francisco Espejo; Jing Shen; Elizabeth Kristjansson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
School-feeding is an important intervention to attract children to school and augment their learning. The benefits of school-feeding cover several domains. Key to the overall assessment of these benefits is understanding how different implementation models compare to each other and to other interventions with similar aims and objectives. Herein, we outline two approaches to aggregating outcomes for school-feeding. One involves a discreet choice experiment to derive utility scores combining outcomes into one measure. The other focuses on quality-adjusted school days as a measure that encompasses the varied benefits from school-feeding. The discrete choice experiment offers a robust method to integrate utility for different benefits. However, it necessitates a complex design. The quality-adjusted school days method has greater simplicity. When developed, different interventions that aim to foster learning could be meaningfully compared.
Keywords: C81; C82; I25; 330; impact; school-feeding; learning; economic indicators